Finding a voice, fighting for rights: the emergence of the transgender movement in Hong Kong 1. - Emerton, Robyn (Inter-Asia Cultural Studies, 2006)
This paper is intended to provide a space for reflection on Hong Kong’s transgender movement at its current stage, with particular reference to the objectives and activities of the Hong Kong Transgender Equality and Acceptance Movement (‘TEAM’). Established in 2002, TEAM was the first organized group of transgender people and supporters in Hong Kong. First, the paper examines the emergence of the transgender movement in Hong Kong, situating the stated objectives of TEAM in the broader social, legal and political context in Hong Kong. It then considers the successes and limitations of TEAM’s activities to date, measured against its objectives. Finally, it examines why Hong Kong’s transgender community has not yet fought for the right to legal recognition of their gender identity, as have transgender individuals and transgender movements in many other countries around the world. In the Asia‐Pacific region these include Australia, Japan, the People’s Republic of China, the Philippines, Singapore, South Korea and New Zealand. Through interviews with members of TEAM, the paper questions whether legal recognition is indeed a concern and/or priority for Hong Kong’s transgender community, and, if so, what prevents Hong Kong transgender people from claiming their right to legal recognition in the courts or through the political process.